The Impact of Problem Posing Strategies on Mathematical Performance, Ability, and Anxiety in Grade 7 Students: A Quasi-Experimental Study - Sangco, Annaliza Requirme; Elpidang, Elan M.; Sangco, Resa Mae R. (Malikussaleh Journal of Mathematics Learning (MJML), 2022)
This study aims to investigate the impact of the problem-posing strategy on the mathematical performance, skills, and anxiety levels of Grade 7 students. Two groups with an equal number of participants were subjected to different instructional strategies: the control group received traditional guided practice, while the experimental group experienced an integrated problem-posing approach. Employing a quasi-experimental design, the study utilized a teacher-made test as both a pre-test and post-test to assess students' academic achievement in mathematics. Additionally, the Modified Abbreviated Math Anxiety Survey (mAMAS) was employed to gauge students' anxiety levels. The experimental group received instruction through the problem-posing method, whereas the control group was taught using traditional guided practice. The findings indicate a significant difference between the two teaching methods, demonstrating that students' mathematics performance is influenced by the instructional strategy used.